2017
DOI: 10.1177/1524838017738725
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Firearms and Intimate Partner Homicide in 15 Nations

Abstract: Intimate partners commit approximately one in three homicides against women worldwide. Little is known about situational factors that contribute to intimate partner homicides (IPH) and how they may differ across nations. This article provides a cross-national exploration of one situational factor, the use of firearms in the commission of homicides, and considers whether nations have laws designed specifically to keep firearms out of the hands of batterers. We conducted a systematic search of peer-reviewed rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Therefore, directing interventions such as strict, comprehensive gun laws toward IPV offenders may prevent IPH as well as homicide more broadly. Indeed, several nations have legislation that addresses gun ownership among those with histories of IPV (Zeoli et al, 2020); however, due to a lack of data, the effect of such laws on reducing homicide is still unknown. As some research has shown heightened gun laws to be counterproductive to reducing IPH (Roberts, 2009), lawmakers should be cautious about this approach until more data are available.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Therefore, directing interventions such as strict, comprehensive gun laws toward IPV offenders may prevent IPH as well as homicide more broadly. Indeed, several nations have legislation that addresses gun ownership among those with histories of IPV (Zeoli et al, 2020); however, due to a lack of data, the effect of such laws on reducing homicide is still unknown. As some research has shown heightened gun laws to be counterproductive to reducing IPH (Roberts, 2009), lawmakers should be cautious about this approach until more data are available.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Results from this study support the necessity of enforcing this law. Previous research has found an association between limiting IPV perpetrators’ access to firearms and a reduction in IPH (Vigdor & Mercy, 2006; Zeoli & Webster, 2010; Zeoli, Malinski & Brenner, 2017). Limiting potential IPH offenders’ access to lethal means by enforcing laws prohibiting IPV perpetrators from owning guns is a way to decrease incidences of IPH.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, given the concern around firearms-related homicide, particularly in rural regions, we have little to no information about firearms used to kill such as whether they were handguns or long guns, if they were licensed, or had been previously seized from the home, and so on (Zeoli et al 2020). Understanding access to firearms as well as relationship dynamics and life situations are key to prevention, but we seldom get this information from official data sources and they may often not be collected, at least consistently, by national statistical agencies or fatality reviews.…”
Section: Completeness Of Datamentioning
confidence: 99%